Potential of palm oil leaves extract as corrosion inhibitor in carbon dioxide (CO2) environment - Nur Syaznabila, Azmi (2016)
This study describes on effect of palm oil leaves extract as corrosion inhibitor in carbon dioxide corrosion. Corrosion is defined as the process of corroding of a material or metal due to the reaction with its environment. For this study, we focus more on corrosion in carbon dioxide environment. CO2 corrosion is one of the main threats in oil and gas industry and have been recognized as one of the problems in oil and gas production and also transportation facilities for many years. In industry, a huge amount of money is wasted for each year due to metal corrosion usually in piping system. It is informed that, this problem can be prevented with proper corrosion prevention techniques or technologies. In this study, green inhibitor will be used to prevent corrosion. It has been found that green inhibitor could be used as one of the corrosion inhibitor in industry. This is due to the green inhibitor containing heteroatoms with high electron density such as phosphorus, nitrogen, sulfur, oxygen together with double or triple bonds are effective as corrosion inhibitor. Green inhibitor will not cost much and easy to find. Corrosion inhibitor in carbon steel in carbon dioxide environment using Palm Oil leaves is being studied. Electrochemical method with several electrode (anode and cathode) is use as an apparatus to examine the rate of corrosion of metal and the effectiveness of inhibitor, Palm Oil Leaves. Usage of Palm Oil Leaves extract in corrosion is believed can be good inhibitor for corrosion on carbon steel. The objective of this study is to study the corrosion rate of carbon steel in environment in the presence of extraction of palm oil leaves use as corrosion inhibitor by using two different method, which are weight loss method and electrochemical method. The inhibitor’s concentrations are varied from 0 ppm to 25 ppm. From the experiment, it is found that increased in inhibitor’s concentration will decreased the corrosion rate.